MEMAHAMI EFEKTIVITAS MANAJEMEN KEUANGAN: Analisis Kualitatif Pada Usaha Mie Ayam di Karangjati Kabupaten Semarang - Zai, Susari; Widagdo, Chrisostomus Susmono (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This research effort aims to examine the role of financial management in the context of chicken maize sellers that function as micro and small. Using a qualitative methodology, the study investigates financial management practices adopted by chicken poultry business owners, in addition to their impact on financial well-being and operational sustainability. This analysis covers aspects such as financial strategy, cash flow administration, investment decision-making, spending regulation, and mitigation of financial risks. The results of this research can offer an in-depth insight into the difficulties and tactics faced by chicken meat vendors in dealing with the financial aspects of their micro and small enterprises. The implications of these findings could serve as a basis for formulating a more robust financial management approach for micro and small operating in the field of culinary trade, those involved in the sale of chicken grain.